PETROLOGY AND METALLOGENY OF THE PALANQUETA MASSIF, BOM FUTURO TIN MINE, RONDÔNIA, BRAZIL: I – GEOLOGY, PETROGRAPHY, AND GEOCHRONOLOGY - Ciotta, Matheus Ramos; Leite Junior, Washington Barbosa [UNESP]; Payolla, Bruno Leonelo; da Silva, Marly Aparecida; Muzzolon, Renato; Bettencourt, Jorge Silva (UNESP - Universidade Estadual Paulista, 2024)
The Palanqueta massif occurs in the Rondônia Intrusive Suite (1026-974 Ma) domain in the Rondônia tin province (SW Amazonian Craton). The massif represents a multiphase pluton intruded in a high crustal level. Geologic mapping on 1:2000 scale defined five granitic units, that are represented by one equigranular biotite-alkali-feldspar granite (ca. 1026 Ma) and four Li-Fe mica-and topaz-bearing alkali-feldspar granites (ca. 1000 Ma), which are distinguished by textural aspects (inequigranular, porphyritic I, porphyritic II and miarolitic). The Li-Fe mica and topaz-bearing granites show textural and mineralogical characteristics of peraluminous rare-metal granites. Mineralized greisen bodies (pipes and veins) in rare metals (Sn and W) and base metal (Cu, Pb e Zn) are mainly associated with porphyritic II facies.
PETROLOGIA E METALOGENIA DO MACIÇO PALANQUETA, MINA DE ESTANHO BOM FUTURO, RONDÔNIA, BRASIL: I-GEOLOGIA, PETROGRAFIA E GEOCRONOLOGIA
Keywords: Brazil; Rapakivi granite; Rare-metal deposit; Rondônia Tin Province; Topaz-bearing granite